Methodological Issues in Court Research: Pretrial Release Decisions for Federal Defendants - Hagan, John (1983)
Combining elements of “response as outcome” studies and “response as process” studies overcomes deficiencies resulting from methodological bifurcation, improves our understanding of court outcomes, and leads to theoretical transformation. Using observational and in-depth interview data to inform hypotheses and to create contextual variables, we develop and test models of the pretrial release decision for federal defendants. These models suggest that the emphasis in outcome research on defendants' ascribed status characteristics has been exaggerated. It is asserted that too little attention has been devoted to processual factors, including labeling, and to jurisdictional and organizational factors determining court outcomes